2012
DOI: 10.1001/archdermatol.2011.1895
|View full text |Cite
|
Sign up to set email alerts
|

Maggot Therapy for Wound Debridement

Abstract: To study the efficacy of bagged larvae on wound debridement compared with conventional treatment. Design: Randomized, multicenter, controlled, prospective phase 3 trial with blinded assessment of outcome measures by a single observer. Setting: Two hospital referral centers in Caen and Lyon, France. Patients: Random sampling of 119 patients with a nonhealing, sloughy wound 40 cm 2 or smaller, less than 2 cm deep, and an ankle brachial index of 0.8 or higher. Intervention: During a 2-week hospital stay, patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Wounds were evaluated on days 8, 15, and 30 [25]. Wound slough was significantly less in the maggot-treated arm by day 8 (54.5% versus 66.5%; P = 0.04), but by day 15 that difference disappeared.…”
Section: Resultsmentioning
confidence: 99%
“…Wounds were evaluated on days 8, 15, and 30 [25]. Wound slough was significantly less in the maggot-treated arm by day 8 (54.5% versus 66.5%; P = 0.04), but by day 15 that difference disappeared.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were identified for the review with a total of 580 participants [ 12 , 16 , 17 , 18 , 19 ]. Of the five studies, three were randomized controlled trials (RCTs) [ 12 , 18 , 19 ], one was a retrospective trial [ 17 ], and one was a prospective cohort study [ 16 ]. Two studies were conducted in the USA [ 16 , 17 ], two in the UK [ 18 , 19 ], and one in France [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the five studies, three were randomized controlled trials (RCTs) [ 12 , 18 , 19 ], one was a retrospective trial [ 17 ], and one was a prospective cohort study [ 16 ]. Two studies were conducted in the USA [ 16 , 17 ], two in the UK [ 18 , 19 ], and one in France [ 12 ]. The number of samples in the studies ranged from 28 [ 17 ] to 267 [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autolytic debridement can be slow and can take a long time to be effective (84). Enzymatic debridement finds use when other techniques are not feasible during the initial management of a chronic wound (85). Mechanical (wet-to-dry) debridement damages healthy granulation tissue (86).…”
Section: Wound Bed Debridementmentioning
confidence: 99%